The recent growth boom in developing economies: The role of services - Diao, Xinshen; McMillan, Margaret S.; Rodrik, Dani (Overseas Development Institute, 2017)
This note draws heavily on the recent paper ‘The recent growth book in developing economies: a structural change perspective’ by Xinshen Diao, Margaret McMillan and Dani Rodrik (2017). Although the paper is not focused on the services sector per se, we may draw two broad conclusions about the role of the services sector in economic growth in developing economies from this paper. We focus on country-specific growth accelerations, which started as early as 1988 and as late as 2003 and last for at least seven years. First, the services sector has contributed to labour productivity growth in developing economies through structural change (primarily Africa) and through productivity improvements within the services sector (primarily Latin America) and sometimes through both channels (primarily East Asia). Second, in many African countries, within-sector productivity growth in the services sector (and in most other sectors, with the exception of agriculture) has been weak and sometimes negative. We argue that one reason for the differences across regions relates to the characteristics of the growth boom and caution that, without within-sector productivity improvements in services and manufacturing, structural, change-led growth will peter out in Africa.